Ride through capabilities of load during voltage sag/swell and power interruption with zigzag transformer - Hafidz, S. A.; Basu, K. P. (2008)
Single-phase voltage sag or swell of a 3-phase system due to one phase to ground fault, capacitor switching or any other reason is to be mitigated immediately for satisfactory operation of all the equipments. A 3-phase zigzag-winding transformer connected across a 3-phase load may mitigate the voltage sag or swell at any one phase of the load. The phase subjected to voltage sag or swell is disconnected from the source first, while the two healthy phases remain connected to the source. The zigzag transformer immediately rebuilds the voltage across the load of the open phase and allows the current to flow to the open phase load. Very low value of zero sequence impedance of the zigzag transformer produces very small voltage drop and the open phase voltage nearly equals the normal voltage. Very short interruption of supply takes place in the affected phase during the transfer of supply to the healthy phases. Proper value of capacitor, connected across the dc load, or the de link capacitor in a converter system for ac load provides the ride through capability of the highly sensitive load during the period of voltage sag/swell or 1-phase power interruption.